Acceptability of emergency contraception in Brazil, Chile, and Mexico. 2 - Facilitating factors versus obstacles Aceitabilidade da anticoncepção de emergência no Brasil, Chile e México. 2 - Fatores que poderiam facilitar ou dificultar sua introdução - Soledad Díaz; Ellen Hardy; Gloria Alvarado; Enrique Ezcurra (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
A multi-center study was performed in Brazil, Chile, and Mexico to identify factors that may facilitate or hinder the introduction of emergency contraception (EC) as well as perceptions concerning emergency contraceptive pills. Background information on the socio-cultural, political, and legal context and the characteristics of reproductive health services was collected. The opinions of potential users and providers were obtained through discussion groups, and those of authorities and policymakers through semi-structured interviews. Barriers to introduction included: perception of EC as an abortifacient, opposition by the Catholic Church, limited recognition of sexual and reproductive rights, limited sex education, and insensitivity to gender issues. Facilitating factors were: perception of EC as a method that would prevent abortion and pregnancy among adolescents and rape victims; interest in the method shown by potential users as well as by some providers and authorities. It appears possible to reduce barriers through support from segments of society committed to improving sexual and reproductive health and adequate training of health care providers. Foram identificados fatores que poderiam facilitar ou dificultar a introdução da anticoncepção de emergência (AE) no Brasil, Chile e México. Foram levantadas informações sobre o contexto sócio-cultural, político e legal bem como sobre as características dos serviços da saúde reprodutiva. As opiniões de potenciais usuários e possíveis provedores foram obtidas por meio de grupos de discussão, e as das autoridades e outras pessoas influentes por intermédio de entrevistas semi-estruturadas. Os obstáculos incluíram: percepção da AE como abortiva; oposição da Igreja Católica; pouco reconhecimento dos direitos sexuais e reprodutivos; pouca educação sexual; e falta de sensibilidade frente às questões de gênero. Os facilitadores foram: percepção da AE como um método que poderia prevenir o aborto e a gravidez entre adolescentes e vítimas de estupro; interesse no método mostrado por potenciais usuárias, bem como por alguns provedores e autoridades. Parece possível reduzir as barreiras identificadas com o apoio dos segmentos da sociedade comprometidos com a melhora da saúde sexual e reprodutiva, e com o treinamento adequado dos provedores de saúde.